Quantitative bead–based multiplex assay for simultaneous determination of IgG concentrations of pertussis toxin, filamentous hemagglutinin, pertactin, diphtheria, tetanus, Haemophilus influenzae b, and hepatitis B in human serum samples - Rathod, Vishal; Katke, Sagar; Patil, Sumant; Bhandare, Sachin; Kadam, Laxmikant; Gautam, Manish; Gumma, Prabhu; Kumar, Krishna Manoj; Hassall, Laura; Asokanathan, Cathy; Douglas-Bardsley, Alex; Markey, Kevin; et al. (Frontiers in Immunology, 2025)
BackgroundMultiplex serological assays provide opportunities for seroprevalence studies and for evaluating antibodies post-vaccination. In this report, we describe the development and validation of a seven-plex bead-based assay for quantifying human immunoglobulin G (IgG) antibodies against pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin (PRN), diphtheria toxoid (DT), tetanus toxoid (TT), Haemophilus influenzae b (Hib), and hepatitis B (Hep B) using international reference standards.MethodsExisting international human reference sera standards are tailored for monoplex assays and, therefore, require characterization for multiplex assays. The reference standards for pertussis (06/142), diphtheria (10/262), tetanus (13/240), Hib (09/222), and Hep B (07/164) were characterized for their suitability in the assay. The purified antigens (PT, FHA, PRN, DT, TT, Hib, and Hep B) were coupled to spectrally unique magnetic carboxylated beads. The method was validated according to the United States Food and Drug Administration (US FDA), European Medicines Agency (EMA), and International Council for Harmonization Multidisciplinary (ICH M10) guidelines. Validation parameters, such as precision, accuracy, dilution linearity, assay range, robustness, and solution stability, were assessed.ResultsAn equi-mix of an international reference standard for Hep B (07/164) and Hib (09/222) provided the best dynamic range for the seven-plex assay. Method validation was conducted using a panel of human serum samples that included samples from vaccinated healthy volunteers, non-vaccinated volunteers, negative controls, and international reference standards. Assay specificity using inhibition experiments demonstrated specificities of 98%, 95%, 93%, 98%, 97%, 97%, and 98% for DT, TT, FHA, PRN, PT, Hib, and Hep-B, respectively. Spike recoveries of 80%–120% were demonstrated in different matrices, including those of hemolytic and lipemic sera samples. The precision and accuracy were confirmed by evaluating a panel of human serum samples obtained from vaccinated individuals. The assay demonstrated coefficients of variation (CV) of ≤ 20% across all assays, regardless of run, day, or analyst. This method demonstrated strong agreement with conventional commercially available assays, highlighting the advantages of multiplexing over traditional enzyme-linked immunosorbent assays (ELISAs).